Performance and changes in body composition of broiler chickens depending on feeding regime and sex - Eva Tůmová; Darina Chodová (Czech Journal of Animal Science, 2018)
The differences in the performance, carcass parts, and internal organs of broiler chicken females and males fed ad libitum or restricted by 80 and 65% ad libitum were evaluated. Ross 308 males and females (2430 chickens) were fed ad libitum (ADL) or were restricted in days 8-14 of age by 80% ADL (R1) and 65% ADL (R2), respectively. Feed restriction depressed the live weight (P ≤ 0.001) in both sexes. Both sexes compensated for growth, and at the end of the fattening at 35 days, the restricted males (-3% R1 and -6% R2) and females (-3% R1 and -4% R2) were not significantly lighter than the ADL chickens. Feed intake was lower (P ≤ 0.001) in females than in males, and feed restriction and sex did not affect the feed conversion ratio. The growth of internal organs as early-developing tissues (heart, gizzard, liver) was less affected than the growth of late-developing tissues (breast, thigh, abdominal fat). Restricted males and females had more abdominal fat than the ad libitum chickens (P ≤ 0.05). Differences in allometric growth between males and females were in the liver, breast, and thigh. At the end of the experiment, restricted males had a higher weight of breast and thigh, whereas in females, the weights of both parts were similar to those of the ADL group. During the restriction period, the growth of internal organs is given priority compared to muscles, which was confirmed by allometric growth. Males showed a higher compensatory growth, including the growth of breasts and thighs.